Complex visual hallucinations and attentional performance in eye disease and dementia: a test of the Perception and Attention Deficit model. (5th April 2013) - Makin, S. M.; Redman, J.; Mosimann, U. P.; Dudley, R.; Clarke, M. P.; Colbourn, C.; Collerton, D.
Abstract : Objective: This study aimed to test the prediction from the Perception and Attention Deficit model of complex visual hallucinations (CVH) that impairments in visual attention and perception are key risk factors for complex hallucinations in eye disease and dementia. Methods: Two studies ran concurrently to investigate the relationship between CVH and impairments in perception (picture naming using the Graded Naming Test) and attention (Stroop task plus a novel Imagery task). The studies were in two populations—older patients with dementia ( n = 28) and older people with eye disease ( n = 50) with a shared control group (n = 37). The same methodology was used in both studies, and the North East Visual Hallucinations Inventory was used to identify CVH. Results: A reliable relationship was found for older patients with dementia between impaired perceptual and attentional performance and CVH. A reliable relationship was not found in the population of people with eye disease. Conclusions: The results add to previous research that object perception and attentional deficits are associated with CVH in dementia, but that risk factors for CVH in eye disease are inconsistent, suggesting that dynamic rather than static impairments in attentional processes may be key in this population. Copyright © 2013 John Wiley & Sons, Ltd.